Reflecting Teacher’s Strategies for Teaching Speaking in Online Learning: A Case Study - Ridha Mardiani; Herrisyandhi Dirgantara (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2022)
Teaching Speaking during Pandemic COVID-19 has forced a female English teacher to conduct it in an online setting.  This required the teacher to implement strategies to help the students learn optimally. She tried to shift her teaching strategies from her traditional classroom strategies to online teaching strategies. Using a case study as the method employed in this research, carrying out classroom observation, conducting teacher interviews, and writing teacher’s journals as the instruments to obtain the data. The teacher’s reflection was made based on a reflective teaching framework in which the teacher’s beliefs and practices are carefully analyzed to see the strategies employed by the teacher. The result shows that her belief in teaching speaking is to motivate and stimulate the students to speak some English words, sentences, or dialogues; drilling and role-playing added by online YouTube videos as her main techniques in teaching speaking. By writing her teaching journal, she expected to have some enhancement in her teaching, classroom management, and students’ responses. The researchers hope that the result of this research can be used as a reference by other researchers to cope with any challenges that occurred while teaching speaking in online learning.